Coagulase-negative staphylococci clones are widely distributed in the hospital and community - Pinheiro-Hubinger, Luiza [UNESP] (2021)
Coagulase-negative staphylococci (CoNS) may be considered contaminants when isolated from clinical specimens but may also be a cause of true infection. This study aimed to compare the clonality and SCCmec type of a collection of CoNS isolated from blood cultures of inpatients, nasal swabs of healthy individuals, and patients with chronic wounds, all from the same community, using SCCmec typing, pulsed-field gel electrophoresis (PFGE), and MLST. Staphylococcus epidermidis, exhibited high clonal diversity, but hospital and community clusters were observed. Nosocomial S. epidermidis clones belonged to sequence types ST2, ST6, and ST23. Some Staphylococcus haemolyticus clones were found to circulate in the hospital and community, while Staphylococcus saprophyticus exhibited very high clonal diversity. Staphylococcus lugdunensis, Staphylococcus warneri, and Staphylococcus capitis revealed several isolates belonging to the same clone in the hospital and community. The detection of different SCCmec types within the same cluster indicated high diversity. S. epidermidis was associated with SCCmec I and III, S. haemolyticus with I and II, S. capitis with type V, Staphylococcus hominis with mec complex type A and ccr1, and S. warneri and S. saprophyticus with SCCmec I. The generation of elements and new combinations of cassette genes were highly associated with CoNS isolates, suggesting that SCCmec may not be a good marker of clonality in these bacteria.